2022
DOI: 10.1002/cre2.524
|View full text |Cite
|
Sign up to set email alerts
|

Final esthetic result of ceramic restorations cemented with different colors of cement

Abstract: Objective The purpose of this study is to evaluate the color changes of lithium disilicate ceramics when cemented with different brands of cement by varying the thickness of the ceramic. Materials and Methods Forty ceramic discs, shade A2, were fabricated with 0.5 and 0.8 mm thickness. Forty composite resin discs, shade A3, were also produced. The ceramic samples were cemented to the composite resin discs, with two colors of resin cement, Neutral and Warm. A spectrophotometer evaluation was made. Translucency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Furthermore, these results suggest that the ceramic’s thickness variation influences the final color of the restoration. These clinical detectable differences are in agreement with Xing et al [ 67 ], Pires et al [ 47 ], Igiel et al [ 21 ], Czigola et al [ 69 ], Tamam et al [ 44 ], Carrabba et al [ 41 ] and Gomes et al [ 70 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, these results suggest that the ceramic’s thickness variation influences the final color of the restoration. These clinical detectable differences are in agreement with Xing et al [ 67 ], Pires et al [ 47 ], Igiel et al [ 21 ], Czigola et al [ 69 ], Tamam et al [ 44 ], Carrabba et al [ 41 ] and Gomes et al [ 70 ].…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that there is a clinically visible color change when varying the cement, as Xing et al [ 67 ], Pires et al [ 47 ], Dede et al [ 68 ], Pissaia et al [ 27 ], Czigola et al [ 69 ], Gugelmin et al [ 54 ], Hoorizad et al [ 49 ] and Carrabba et al [ 41 ] stated. In a previous study conducted by our team, Gomes et al [ 70 ] concluded, like Tabatabaei et al [ 71 ], that there is a clinically detectable difference between cements.…”
Section: Discussionmentioning
confidence: 89%
“…Then, 44 studies remained for full-text evaluation. From these, 17 studies were excluded because of several reasons (Table S2): (11) there was no comparison between light-cure and dual-cured resin cements, [14][15][16][17][18][19][20][21][22][23][24] (3) the full-text of the manuscript could not be retrieved, [25][26][27] (2) did not use any aging method, 28,29 and (1) was in Chinese. 30 The qualitative analysis was performed on a total of 27 articles.…”
Section: Resultsmentioning
confidence: 99%